1993
DOI: 10.1016/0925-8388(93)90024-h
|View full text |Cite
|
Sign up to set email alerts
|

In situ studies of amorphization of the GeAl and SiAl systems induced by 1 MeV electron irradiation

Abstract: Ge/A1 and Si/A1 bilayer staecimens, as well as A1-2.3 at.% Ge two-phase alloy specimens, were irradiated in situ with 1 MeV electrons at temperatures if's) in the range 10 -190 K in a high voltage electron microscope. At 10 K it is found that for a Ge/AI bilayer specimen amorphization at the interface occurs only when the Ge layer faces the incident electron beam, while for a Si/A1bilayer specimen amorphization occurs regardless of the direction of the incident beam. In this case, the critical fluence for amor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1999
1999
1999
1999

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…This result demonstrates that irradiation amorphization in multilayers can be achieved in the absence of displacement cascades. Amorphization of layered metallic materials by electron irradiation has also been observed by Lin, Seidman, and Okamoto, 15 who amorphized Ge-Al and Si-Al bilayers with a 1 MeV electron beam. They found that a recoil-implantation model explained well their results.…”
Section: B Electron Irradiation Induced Amorphizationmentioning
confidence: 78%
See 3 more Smart Citations
“…This result demonstrates that irradiation amorphization in multilayers can be achieved in the absence of displacement cascades. Amorphization of layered metallic materials by electron irradiation has also been observed by Lin, Seidman, and Okamoto, 15 who amorphized Ge-Al and Si-Al bilayers with a 1 MeV electron beam. They found that a recoil-implantation model explained well their results.…”
Section: B Electron Irradiation Induced Amorphizationmentioning
confidence: 78%
“…At the two intermediate temperatures ͑293 and 373 K͒, no crystalline intermetallic compound diffraction lines appeared during irradiation. At the lowest temperature ͑17 K͒ diffraction lines corresponding to another intermetallic compound (ZrFe 2 ) appeared at 5ϫ10 15 cm Ϫ2 . Figure 8 shows the diffraction patterns obtained at the end of the irradiation time for the longer wavelength Fe-rich samples ͑3X͒.…”
Section: Fe-rich Samples (64 At % Fe)mentioning
confidence: 99%
See 2 more Smart Citations